Gastrodia flexistyloides (Orchidaceae), a new mycoheterotrophic plant with complete cleistogamy from Japan - Suetsugu, Kenji (Phytotaxa, 2014)
A new species, Gastrodia flexistyloides (Orchidaceae: Epidendroideae, Gastrodieae) from Takeshima Island, Kagoshima Prefecture, Japan, is described and illustrated. In its trilobed column with a strongly incurved central lobe, this species shows a close affinity to G. flexistyla from Taiwan, but it is easily distinguished from G. flexistyla by several characteristics, including taller stature during the flowering period and completely cleistogamous flowers with a smaller and narrower perianth tube.